2014
DOI: 10.21890/ijres.76785
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Mathematics Achievement and Retention Scores: A Case of Problem-Based Learning Method

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
41
3
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 11 publications
13
41
3
9
Order By: Relevance
“…As the findings for grade twelve indicated 55.4% of variation in the achievement score was jointly accounted for by enjoyment, motivation, and confidence attitude scales. The remaining 44.6% of the achievement of students in mathematics might be affected by other factors such as inadequate teaching motivation, poor assessment, poor teaching methods [2], and teachers' attitude towards mathematics or their job [39,42,44] When the objective of this study expressed in terms of grade levels, individual contribution of each attitude predictor on the achievement of students, as it can be seen in the above discussions, were greater in grade twelve as compared to grade ten. However, the type of the attitude predictors were similar, namely ES, MS, and CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the findings for grade twelve indicated 55.4% of variation in the achievement score was jointly accounted for by enjoyment, motivation, and confidence attitude scales. The remaining 44.6% of the achievement of students in mathematics might be affected by other factors such as inadequate teaching motivation, poor assessment, poor teaching methods [2], and teachers' attitude towards mathematics or their job [39,42,44] When the objective of this study expressed in terms of grade levels, individual contribution of each attitude predictor on the achievement of students, as it can be seen in the above discussions, were greater in grade twelve as compared to grade ten. However, the type of the attitude predictors were similar, namely ES, MS, and CS.…”
Section: Discussionmentioning
confidence: 99%
“…As long studies history in this area has shows that females had higher performance at lower grade levels (1 -6) but as their grade levels increases especially at the end of eighth grade and after gender differences in performance were pervasive -with males having significantly higher achievement than males [40]. On the contrary, as recent researches has shown that the gender differences in mathematics performance are diminishing and these researches indicated that gender differences in mathematics achievement are reducing and shifting, though males were more likely to get higher mean scores [2].…”
Section: Gender Differences In Attitude and Achievementmentioning
confidence: 99%
“…Others noted that these differences were not consistent. Ajai and Imoko (2015) undertook a study to assess gender differences in mathematics achievement and retention. The study proved that male and female students did not significantly differ in achievement and retention scores, which showed that they are capable of competing in mathematics.…”
Section: Gender and Academic Achievementmentioning
confidence: 99%
“…While several recent studies have identified no differences in the achievements of females and males in mathematics (Ajai & Imoko, ; Bergeron & Gordon, ; Sarouphim & Chartouny, ), substantial literature on gender mathematics achievement indicates that a gender achievement gap exists in mathematics and favors males (Fahle, ; Lubienski, Robinson, Crane, & Ganley, ; Reilly, Neumann, & Andrews, ; Robinson & Lubienski, ; Sohn, ). This gap is also present in the tails of the distribution, especially with high achievers (Pope & Sydnor, ; Robinson & Lubienski, ).…”
Section: Gender and Mathematics Achievementmentioning
confidence: 99%